Leptochilus ornithopus (Polypodiaceae), a new hemiepiphytic fern species from central highlands of Vietnam - Fujiwara, Tao; Quang, Bui Hong; Tagane, Shuichiro; Murakami, Noriaki; Oguri, Emiko (Phytotaxa, 2023)
Leptochilus ornithopus T. Fujiw. & B.H. Quang (Polypodiaceae, Polypodiales) is described as a new species, based on integrated evidence from phylogenetic and morphological examinations. The new species is most similar to L. digitatus and L. longipes but distinguished from both by its having ovate rhizome scales, narrowly cuneate and gradually reduced lamina base, narrowly lanceolate lateral lobes of lamina which are widest at proximal 1/3 or base, and the sori at an angle of 31–38(–40) degree with the midrib.